Sports Education inTurkish Higher Education within European Qualifications Framework - Fehmi Çalık; Kürşad Sertbaş; Serdar Geri (Türk Spor ve Egzersiz Dergisi)
Sports sciences and sports education are applied in various scientific disciplines of Turkish higher education. Sport Sciences are applied in many universities in Europe to sports education students in higher education and to students in other departments for to meet social needs. In this regard, restructuring sports education is a new requirement in Turkey in terms of European sports education cooperation and developments. The aim of this study is to examine European Higher Education Qualities and Turkey's Higher Education Sports Education Process for to set forth an understanding regarding mission and vision in the forthcoming years. ISCED, EASM, and AEHESIS sports education models and European Union education process are analyzed within the scope of the research. Eventually, Turkey is in a restructuring process in terms of physical education and sports education in higher education, Bologna process and qualities. Within the scope of this regulation, anew sports education and basic field qualifications curricula should be updated by considering determination of basic fields. Turkish Higher Education Qualifications Framework (TYÇÇ) basic field qualifications that are formed based on the ISCED concerning Coaching Education, Sports Management and Recreation Departments should be reclassified.